Formation of Catechists – Inspirations from Directory for Catechesis - Zellma, Anna (Studia Warmińskie, 2021)
The formation of catechists plays an important role in the Church’s catechetic work. It has an impact on the quality of evangelisation and catechesis in the contemporary world. The analyses performed in this paper aim at presenting the major aspects of catechist formation according to the approach taken in Directory for Catechesis (2020). To this end, the desk research method was used. The contents of the new catechetic document were analysed. Some references were made to other catechetic documents, studies, and publications on catechist formation in order to reinforce the study conclusions. It allowed for showing both the constant and the new aspects of catechist formation. It was observed that the nature, objectives, criteria, and dimensions of catechist formation do not change. Directory for Catechesis rightly supplements it with new accents, due to social and cultural changes. It is important to enhance the importance of humanities and social sciences, including psychology, pedagogy, sociology, and social communication sciences. Proper emphasis placed on such fields shows their clear pastoral significance. They also play an important role in the organisation of the holistic formation of catechists in particular Churches – at the parish or diocese level and at universities. The analyses have confirmed that the Church cares about the multi-aspect, in-depth, permanent catechist formation, adapted to the social, cultural and religious challenges. Greater emphasis in catechist formation should be placed on gaining experience in their teams. Formation in small groups (catechist communities) involves sharing personal experience of faith, strengthens one’s vocation, helps to develop educational, interpersonal, and communication competence, and makes one capable of accompanying the participants of catechesis.